2014
DOI: 10.1093/brain/awu173
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning in relation to brain amyloid-β in healthy adults with Down syndrome

Abstract: Nearly all adults with Down syndrome show neuropathology of Alzheimer's disease, including amyloid-β deposition, by their fifth decade of life. In the current study, we examined the association between brain amyloid-β deposition, assessed via in vivo assessments of neocortical Pittsburgh compound B, and scores on an extensive neuropsychological battery of measures of cognitive functioning in 63 adults (31 male, 32 female) with Down syndrome aged 30-53 years who did not exhibit symptoms of dementia. Twenty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 33 publications
20
91
0
Order By: Relevance
“…Nonetheless, most individuals with DS have amyloid-positive PET scans by the age of 50 (REFS 45,96,99,100). Amyloid load, as measured by PET, does not correlate well with cognitive function in adults who have DS in cross-sectional studies 45,99 , highlighting the importance of factors other than amyloid in the development of dementia. However, longitudinal imaging studies in this population have yet to be undertaken and may be highly informative 45,99 .…”
Section: Neuropathological Changes In Ad-dsmentioning
confidence: 94%
See 2 more Smart Citations
“…Nonetheless, most individuals with DS have amyloid-positive PET scans by the age of 50 (REFS 45,96,99,100). Amyloid load, as measured by PET, does not correlate well with cognitive function in adults who have DS in cross-sectional studies 45,99 , highlighting the importance of factors other than amyloid in the development of dementia. However, longitudinal imaging studies in this population have yet to be undertaken and may be highly informative 45,99 .…”
Section: Neuropathological Changes In Ad-dsmentioning
confidence: 94%
“…Amyloid load, as measured by PET, does not correlate well with cognitive function in adults who have DS in cross-sectional studies 45,99 , highlighting the importance of factors other than amyloid in the development of dementia. However, longitudinal imaging studies in this population have yet to be undertaken and may be highly informative 45,99 .No NFTs have been reported in AD-DS in the absence of dense-core plaque pathology, which is consistent with the predictions of the amyloid cascade hypothesis. The density of NFTs triples between the fourth and fifth decade of life in AD-DS 77 , mirroring the onset of dementia, and NFT formation rather than amyloid deposition correlates best with cognitive decline 34 , which is consistent with similar findings in LOAD.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Neuroimaging studies have identified typical brain atrophy in patients with DS and AD [12], as well as indicators of dementia correlated with structural and functional findings in individuals with DS without clinical signs of AD but at the age of risk for its development [13]. Nevertheless, recent research indicates that many adults with DS can tolerate the deposition of Aβ with no effects on their cognitive functions [14]. …”
Section: Introductionmentioning
confidence: 99%
“…However, conclusions are limited due to cross-sectional designs (Annus et al, 2016; Handen et al, 2012; Hartley et al, 2014; Nelson et al, 2011), small sample sizes (Handen et al, 2012), and restricted neuropsychological batteries of cognitive functioning (Nelson et al, 2011). In the largest cross-sectional study, and the one with the most extensive battery of directly-administered neuropsychological measures, Hartley et al (2014) found a negative association between neocortical PiB retention and verbal and visual episodic memory, executive functioning, and expressive language in 63 adults with DS (aged 30–50 years) who did not exhibit clinical signs of AD. A handful of studies have also examined neocortical amyloid-β accumulation in the preclinical stages of AD in DS using the PET tracer Florbetapir (Rafii et al, 2015; Sabbagh et al, 2015).…”
mentioning
confidence: 99%